Pengaruh Terapi Relaksasi Otot Progresif Terhadap Penurunan Kram Otot pada Pasien Hemodialisa - Agus Rahmat Yanto Buaya; Otomosi Hulu; Ardin Ndruru; Elis Anggeria (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2022)
Hemodialysis is an exceptionally huge general clinical issue, notwithstanding the extremely significant expense of treatment and treatment. Moderate muscle unwinding is a non-pharmacological treatment that depends on the standard that the activity of muscles on the physiological unsettling influences of the human body diminishes messes. Muscle cramps are disappointment experienced by the gathering without torment, in cirrhotic patients and those going through hemodialysis. The motivation behind this study was to decide the effect of moderate muscle unwinding on lessening muscle cramps in hemodialysis patients. This sort of exploration utilizes quantitative strategies with a semi-trial plan through a one gathering pre-test post-test configuration approach. The populace in this study was 35 patients who experienced cramps. The strategy utilized for testing is soaked inspecting, with the goal that the necessary example is 30 individuals. The aftereffects of the review got added up to 58-63 years, with the male sex. The consequences of the information acquired before the mediation were most of the extreme spasms. After the intercession of gentle squeezing. In light of the reduction in muscle cramps in hemodialysis patients, the worth of sig (2-followed) was 0.00, and that intends that there were contrasts in muscle cramps when the technique.